Angle of twist of a double-bent leaf flexure under torsion - Nguyen, Nghia Huu (Strojniški vestnik, 2018)
This paper describes the rotational displacement of the double-bent leaf flexure subjected to a torsional load. Warping and specifically double partially-restrained warping are considered when the torsion is applied. The warping restraint factor for partially-restrained warping is also considered. Castigliano's theorem is applied to derive the theoretical equations of the angle of twist. The results for the fully restrained, partially restrained, and free warping cases are compared and verified with finite element analysis (FEA). A sensitivity analysis over the length, width, and thickness is performed and the results are compared with FEA. The errors between the theory result with the warping restraint factor (K = 0.5) and those of FEA are the lowest, below 5%. This suggests that the angle of twist of the double-bent leaf flexure under torsion is accurately predicted by considering double partially-restrained warping.
Keywords: analiza po metodi končnih elementov; Castigliano's theorem; Castiglianov teorem; delno ovirano vbočenje; double-bent leaf flexure; dvakrat upognjeno listnato vzmetno vodilo; faktor oviranja vbočenja; finite element analysis; partially restrained warping; torsion; torzija; warping restraint factor